Peptides for Diagnosis and Treatment of Colorectal Cancer - Shapira, S.; Fokra, A.; Arber, N.; Kraus, S. (Current Medicinal Chemistry, 2014)
Colorectal cancer (CRC) is a major health concern worldwide, as it is the third most frequently diagnosed cancer and the second leading cause of cancer-related death. There are a number of treatment options for CRC, however many of them are disappointing. Therefore, significant efforts are directed towards the development of new biological therapies with improved efficacy. The use of peptides in CRC treatment holds promise as emerging novel anti-cancer agents. Targeted therapy based on the use of peptides that can directly target tumor cells without affecting normal cells is evolving as an alternative strategy to conventional therapies and particularly, chemotherapy. The main advantages of peptides are their relatively easy and rapid synthesis process, and the vast possibilities for chemical modifications that can be exploited for novel peptide design and improved delivery. Peptides can be utilized directly as cytotoxic agents or indirectly as they can act as carriers of cytotoxic agents, drugs, or radioisotopes by specifically targeting tumor cells. They can also be used for diagnostic purposes. Current research focuses on developing peptides that can serve as tumor targeting moieties, permeabilize membranes to induce cytotoxicy, radiolabeled peptides, and peptide vaccines. In addition, improving targeting to tumors, reducing side effects, due to non-specific toxicity, and unraveling the pharmacokinetic characteristics of potential peptides, for either therapeutic or diagnostic use, are also subjects of intensive investigation. This review provides a brief overview on the role of peptides in CRC diagnosis and therapy that are currently being investigated, and their potential applications in the clinical setting.
Keywords: cytotoxic T-lymphocytes (CTLs)